2007
DOI: 10.2967/jnumed.107.042143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Probable or Possible Dementia with Lewy Bodies Using 123I-IMP Brain Perfusion SPECT, 123I-MIBG, and 99mTc-MIBI Myocardial SPECT

Abstract: We evaluated the diagnostic usefulness of combination studies with a statistical mapping method in N-isopropyl-p-123 Iiodoamphetamine ( 123 I-IMP) brain perfusion SPECT, cardiac sympathetic nerve function by 123 I-metaiodobenzylguanidine ( 123 I-MIBG), and myocardial function by electrocardiographically gated 99m Tc-sestamibi ( 99m Tc-MIBI) SPECT for patients with probable or possible dementia with Lewy bodies (DLB). Methods: Twelve patients with probable DLB (7 male, 5 female; mean age 6 SD, 72.3 6 5.63 y; ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The comprehensive computer literature search from the PubMed/MEDLINE and Embase databases revealed 71 articles (Fig 1). Reviewing titles and abstracts, 41 articles were excluded because they did not present any diagnostic information; 30 articles were selected 12–41 . These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive computer literature search from the PubMed/MEDLINE and Embase databases revealed 71 articles (Fig 1). Reviewing titles and abstracts, 41 articles were excluded because they did not present any diagnostic information; 30 articles were selected 12–41 . These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 .…”
Section: Resultsmentioning
confidence: 99%
“…These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 . From these 31 articles potentially eligible for inclusion, after reviewing the full‐text article, one study was excluded as case report; 23 one article was excluded because sensitivity and specificity of MIBG scintigraphy in the subset of DLB population could not be calculated for insufficient data; 12 seven articles were excluded because there was an overlap of patient data in other studies; 20,24,26,29,31,34,40 12 articles were excluded because MIBG scintigraphy was not performed in patients with other dementia than LBD; 13–16,19,21,25,28,32,35,36,38 two articles were excluded because less than 6 patients with DLB were included 37,42 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SPECT imaging was also used in combination with other measures to better detect changes in DLB. Several studies (Hanyu et al, 2006b;Inui et al, 2007;Novellino et al, 2010;Tateno et al, 2008b) which combined SPECT and (1,2,3)I-metaiodobenzylguanidine myocardial (MIBG) scintigraphy reported that the accuracy power in the diagnostic process of DLB resulted increased. Furthermore, Goto and colleagues (Goto et al, 2010) proposed to combine the computation of ratios on perfusion SPECT with MRI volumetric data (hippocampal, occipital, and striatal structures) to discriminate between DLB and AD.…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…In extreme cases, typical DLB patients without apparent uptake decreases in the occipital regions tend to be branded as ‘DLB unlikely’ only because of negative SPECT findings. It should be kept in mind that low uptake in the occipital areas is a feature distinguishing DLB from Alzheimer's disease (AD) [4,5,6,7,8,9,10,11], and that it is not a ubiquitous finding among patients with DLB [9,12,13]. Compared with normal controls, DLB patients may rather show lowered uptake in the frontal, parietal, temporal and thalamic regions [14].…”
Section: Introductionmentioning
confidence: 99%